Estrategia metodológica basada en actividades acuáticas para potenciar la rehabilitación y el desarrollo motor humano en los niños con capacidades educativas diferentes del centro educativo especial “Divino niño Jesús “del cantón Saraguro, provincia de Loja, durante el año lectivo 2012-2013 - Yanza Silva, Víctor Alfredo (2015)
This paper investigates How empower through water sports rehabilitation and human motor development in children with different educational capacities with Down syndrome, the special school Divine Child Jesus? The overall objective of the research is to design a methodological strategy based on water activities, allowing promote rehabilitation and human motor development of children with Down Syndrome. As it is proposed to identify specific theoretical and methodological references related to rehabilitation and human motor development in children with different educational capacities with SD, through aquatic activities; identify disabilities in children present School "Divine Child Jesus" and the methods and procedures used by teachers to rehabilitate their motor development; selecting aquatic activities that enhance the rehabilitation and human motor development in children with Down syndrome and integrated into a methodological strategy; and assess the results to be obtained as a result of the application of the proposed methodological strategy. The paradigm in which it is located is qualitative. Conclusions, design, construction and application of aquatic rehabilitation methodological strategy for improving the human motor development in disability cases with Down syndrome; achieving improvements in altered muscle tone, postural control, balance and raising the mood of the child thanks to the playful and recreational approach to water; It is considering that its implementation serves to promote the rehabilitation of motor development, coexistence among them, encouraging cooperation and assistance among their peers